Pengaruh Layanan Bimbingan Kelompok Teknik Sosiodrama Terhadap Penyesuaian Diri Siswa Kelas VII Di SMP Negeri 2 Pegandon - Rista Apriyanti; Siti Fitriana; MA Primaningrum Dian (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This research was motivated by students experiencing problems with obstacles in adjusting themselves, such as not being able to adjust well. This happens when there are some students who are still alone, do not adapt to the environment, lack self-confidence, feel inferior to other students, are embarrassed when meeting or talking to the opposite sex. The aim of this research is to determine whether there is an influence of group guidance services using sociodrama techniques on students' adjustment between the experimental group and the control group. This type of research is quantitative. The research method used is True Experiment Design using a pretest and posttest control group design model. The population in this study was class VII students at SMP Negeri 2 Pegandon, totaling 150 students and the sample for this study as a try out class was selected using a random sampling technique, namely class VII B with a total of 30 students then divided into two groups each of 15 students in the experimental group and 15 students in the experimental group. control group. The data in this research was obtained through interviews and psychological scales. Based on the t test calculation, the tcount result was 3.7, while ttable with db=(n1+n2)-2= (15+15)-2 =28 and a significance level of 5% (0.05) was 2.048. This means that tcount (3.7) > ttable (2.048), then the alternative hypothesis (Ha) is that there is an influence of the Sociodrama Engineering Group Guidance Service on the Self-Adjustment of Class VII Students at SMP N 2 Pegandon. Keywords: Group guidance, Sociodrama, Personal Adjustment